OPTIMASI PORTOFOLIO DAN ANALISIS RISIKO SAHAM IDX30 MENGGUNAKAN K-MEANS, MARKOWITZ DAN VAR - Basri, Hanisa; Wibowo, Wahyu (Jurnal Ilmiah Akuntansi dan Keuangan (JIAKu), 2025)
Investment involves growing personal wealth through asset value appreciation. From 2020 to 2024, Indonesians’ interest in investing rose by 228.52%. However, the 2022 National Survey on Financial Literacy and Inclusion (SNLIK) showed a decline in the capital market literacy index, dropping from 4.92% in 2019 to 4.11% in 2022. This highlights a gap between investment interest and financial knowledge. To address this issue, research was conducted to optimize portfolio formation using the K-Means and Markowitz methods, with risk measured through Value at Risk (VaR) Backtesting. The Markowitz method minimizes risk for a given return level, helping investors meet financial goals efficiently. The analysis used stocks from the IDX30 index, known for liquidity, strong fundamentals, and large market caps. The study produced an optimal portfolio with a 16% expected return and a 32.827% annual risk. The stock allocation is: AKRA (8.444%), AMRT (6.135%), BBCA (39.900%), BMRI (17.385%), BBNI (11.410%), ICBP (14.448%), and MEDC (2.278%). The portfolio's maximum loss was -1.628%, lower than any individual stock, demonstrating the model's accuracy and reliability in managing risk while maintaining return potential.